The Effect of Class Scheduling on The Students’ English Performance - Rachmah Ganif Fiani; Sherly Putri Qirani; Vivian Taka Istighfarin (Edulitics (Education, Literature, and Linguistics) Journal, 2021)
The study focuses on the effect of the class scheduling toward the students’ English performance during the latest policy of new normal face to face learning. The research method used was case study research design. The researchers used an interview and questionnaire as the research instrument to gain the data. The subject of the research was X MIPA 1 to X MIPA 8 in SMA Negeri 1 Gedangan; in specific number were 15 students as the interviewee and 130 students who were willing to participate filling the survey. The data analysis technique was descriptive analysis with the percentage technique from the questionnaire analysis result to validate the outcome of the research. The results of this study showed that the school has prepared an effective schedule yet the indiscipline of teachers and students who are not able to implement the class scheduling in accordance with the provisions of the applicable rules. Therefore, students’ English performance was disrupted due to the implementation of inefficient time allocations. Thus, the school must optimize teacher performance in managing time and improve student performance so that the short lesson hours can be more effective and help students learn without any interference from time allocation problems, class scheduling, and other internal factors.